The Bioactive Compounds and Antioxidant Activity of Food Products of Rhizophora stylosa Fruit (Coffee and Tea Mangrove) - Dewi Indah Miranti; Hideaki Ichiura; Yoshito Ohtani (International Journal of Forestry Research)
The objective of this study is to investigate the bioactive compounds and antioxidant activity of coffee and tea mangrove (locally known in Indonesia) produced from the fruit of Rhizophora stylosa. Furthermore, three raw materials of coffee mangrove were also investigated to clarify their potencies. The crude extracts of five samples were subjected to antioxidant assay using DPPH. The results show that the extract of tea mangrove has the strongest activity; then, it was successfully fractionated using different polarity of solvents and yielded acetone and methanol fractions that had high antioxidant activity. The acetone fraction was purified and gave fractions A1, A2, A3, A4, A5, and A6, but only A2 and A3 indicated antioxidant activity and, therefore, they were subjected to further purification. Fractions A3 (caffeine) and A2 gave AS1 (N,N-dimethyl-L-alanine), AS2 (quercetin-3-O-galactopyranoside), AS3 (dodecanoic acid), and AS4 that had the similar 1H-NMR spectrometric results with AS2, while the methanol fraction did not exhibit clear peaks on the chromatogram by HPLC. Therefore, the precipitation method was conducted to purify this fraction, and the precipitate was analyzed by NMR spectra. The results from 1H and 13C NMR indicate that this fraction is a typical polymer of condensed tannins, containing procyanidin and prodelphinidin units.